Treatment for Cancer Patients with Oral Mucositis: Assessment Based on the Mucositis Study Group of the Multinational Association of Supportive Care in Cancer in International Society of Oral Oncology (MASCC/ISOO) in 2013 and Proposal of Possible Novel Treatment with a Japanese Herbal Medicine - Miyano, Kanako; Ueno, Takao; Yatsuoka, Wakako; Uezono, Yasuhito (Current Pharmaceutical Design, 2016)
The cancer patients who received chemotherapy, radiotherapy, hematopoietic stem cell transplant and terminal care often have a wide range of stomatitis, which induces severe pain and limits fundamental life behaviors such as “eating, drinking and talking”. In addition, oral mucositis frequently leads to systemic infection through opportunistic microorganisms, which causes extension of hospitalization. Severe oral mucositis often causes cancer patients to partially or completely discontinue/modify cancer therapy regimen, which adversely affects the curative effects of cancer. Therefore, the control of oral mucositis is important and indispensable for improvement of quality of life and prognosis. In this review, we introduce recent trends of the oral mucositis management in cancer patients, according to the following sentences; 1) pathophysiological mechanisms of oral mucositis, 2) assessment, 3) risk factors, 4) prevention and treatment, and 5) development of novel therapy for oral mucositis.
Keywords: chemotherapy